International Union of Basic and Clinical Pharmacology CIII: Chemerin Receptors CMKLR1 (Chemerin(1)) and GPR1 (Chemerin(2)) Nomenclature, Pharmacology, and Function - Kennedy, Amanda J. (Pharmacol Rev, 2018)
Chemerin, a chemoattractant protein and adipokine, has been identified as the endogenous ligand for a G protein–coupled receptor encoded by the gene CMKLR1 (also known as ChemR23), and as a consequence the receptor protein was renamed the chemerin receptor in 2013. Since then, chemerin has been identified as the endogenous ligand for a second G protein–coupled receptor, encoded by the gene GPR1. Therefore, the International Union of Basic and Clinical Pharmacology Committee on Receptor Nomenclature and Drug Classification recommends that the official name of the receptor protein for chemokine-like receptor 1 (CMKLR1) is chemerin receptor 1, and G protein–coupled receptor 1 is chemerin receptor 2 to follow the convention of naming the receptor protein after the endogenous ligand. Chemerin receptor 1 and chemerin receptor 2 can be abbreviated to Chemerin(1) and Chemerin(2), respectively. Chemerin requires C-terminal processing for activity, and human chemerin21–157 is reported to be the most active form, with peptide fragments derived from the C terminus biologically active at both receptors. Small-molecule antagonist, CCX832, selectively blocks CMKLR1, and resolvin E1 activation of CMKLR1 is discussed. Activation of both receptors by chemerin is via coupling to G(i/o), causing inhibition of adenylyl cyclase and increased Ca(2+) flux. Receptors and ligand are widely expressed in humans, rats, and mice, and both receptors share ∼80% identity across these species. CMKLR1 knockout mice highlight the role of this receptor in inflammation and obesity, and similarly, GPR1 knockout mice exhibit glucose intolerance. In addition, the chemerin receptors have been implicated in cardiovascular disease, cancer, steroidogenesis, human immunodeficiency virus replication, and neurogenerative disease.